Echocardiographic Evaluation of His Bundle Pacing in Patients with Prolonged PR Intervals - Fry, Ethan; Ayoub, Karam; Sorrell, Vincent L; Souza, Joseph; Hesselson, Aaron; Leung, Steve; Ellison, Kristin (Cardiology and Cardiovascular Medicine, 2023)
Background: Patients with PR intervals >240ms have atrio-ventricular (AV) dyssynchrony, which can increase risk of atrial fibrillation and allcause mortality. When requiring pacing, long AV delays (AVDs) have been programmed to avoid ventricular dyssychrony. His bundle pacing (HBP) may provide improved AV synchrony in patients with prolonged PR. Methods: 10 patients with sinus node dysfunction and prolonged PR who received HBP were studied. Real-time echocardiographic was performed with 3 pacemaker modes (RV septal, non-selective HBP, and selective HBP) using the following pacemaker settings: control (no ventricular pacing), pacing with AVD of 180ms, 150ms, 120ms, 100ms, and 70ms. Echocardiographic Doppler measurements: EA/RR, >40% = AV synchrony; E/e’, <8 = normal left atrial pressure; pulmonic-to-aortic preejection time difference, <40ms = interventricular synchrony; septal-tolateral wall activation time difference, <56ms = intraventricular synchrony; and LVOT VTI. Unpaired T test was used to evaluate for significance. Exclusion criteria: persistent atrial fibrillation, second-degree AV block. Results: Compared to control programming, HBP showed a 31.5% increase in EA/RR time, a decrease in E/e’ of 26.9%, and an increase in the LVOT VTI of 21.3%. Compared to RV septal pacing, there was a similar increase in LVOT VTI. These findings met statistical significance and were considered optimal based on Doppler echocardiography findings primarily at AVDs of 150ms and 120ms. Comparisons between selective and non-selective pacing were not significantly different. Conclusion: Compared to controls and RV septal pacing, physiologic His bundle pacing was shown to increase markers of AV synchrony and LV stroke volume while maintaining ventricular